Mobilizing the fishing industry to address data gaps created by shifting species distribution - Heimann, Thomas; Verkamp, Hannah; McNamee, Jason; Bethoney, N. David (Frontiers in Marine Science, 2023)
Globally, climate change is inducing range shifts and expansions for numerous species. For commercially exploited species, such as those in directed fisheries, this can cause numerous issues with management and jurisdictions as the species shift and expand into areas at levels previously unseen. The black sea bass (Centropristis striata) fishery has rapidly expanded in the northern Atlantic. Over the past decade commercial landings have more than doubled in the New England and Mid-Atlantic regions. This increase is related to a northward shift in the species’ center of biomass and range expansion. There is a crucial need for increased data in this species’ northern range. Oftentimes, large-scale fisheries data collection is limited by available resources and the difficulty of collecting data at-sea. Citizen science, such as fishing industry-based Research Fleets, represent a cost-effective option to help overcome these limitations and allow for the rapid collection of large amounts of data. The Commercial Fisheries Research Foundation and Rhode Island Department of Environmental Management established the Black Sea Bass Research Fleet in 2016. The Research Fleet is composed of fishers representing a variety of gear types who collect fishery-dependent data on black sea bass at-sea on a custom tablet application. In five years, 20 captains participated in the Research Fleet and collected length, visually-identified sex, and disposition data on 40,939 individual black sea bass throughout southern New England and into the Mid-Atlantic Bight. Catch, effort, and basic environmental data from 2,288 sampling sessions have been collected alongside this biological data. We apply the collaborative Research Fleet approach to a finfish for the first time and evaluate its performance over the first five years of sampling through participant engagement, magnitude of data collection, and interest in collected data. Further, we introduce the next steps being undertaken to incorporate the collected data into the management framework. This project illustrates that a science-industry research collaboration such as the Black Sea Bass Research Fleet can consistently collect large amounts of fishery-dependent data on black sea bass, and highlights a mutual interest among fishers, scientists, and managers to expand the collection of reliable data on this important species.